Language and social services in rural North West the status of Setswana - Nkashe, Esther (Rhodes University, Faculty of Humanities, School of Languages, 2012)
This study seeks to support the thesis that African indigenous languages in South Africa should enjoy equal treatment in terms of the South African Constitution. Therefore, it will explore and find ways and means of how the South African government can reach out to rural communities with inadequate English proficiency, in an English-dominated South Africa, by breaking down the existing language barriers and curbing social inequalities. Language rights, like any other human rights, should be protected, as enshrined in the new democratic Constitution of South Africa.
Keywords: Tswana language; Linguistic rights -- South Africa -- North-West; Linguistic rights; Language policy -- South Africa -- North-West; Linguistic minorities -- South Africa -- North-West; Multiculturalism -- South Africa -- North-West; Language and languages -- Political aspects -- South Africa -- North-West